2001
DOI: 10.1016/s0735-1097(00)01091-3
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of stenotic or occluded iliofemoral veins and inferior vena cava using intravascular stents: re-establishing access for future cardiac catheterization and cardiac surgery

Abstract: Stenotic/obstructed IFV and IVC may be reconstructed using stents to re-establish venous access to the heart for future cardiac catheterization and/or surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…However, it is problematic for future catheterizations and catheter interventions. In such cases stenting of the iliofemoral veins up to the inferior vena cava is possible and the procedure has been described by Ing and associates [170,171]. Immediate and follow-up results look satisfactory [172] as documented in one study; 70 systemic venous stents were placed in 33 patients and a significant increase in vessel diameter was observed.…”
Section: Systemic Veinsmentioning
confidence: 99%
“…However, it is problematic for future catheterizations and catheter interventions. In such cases stenting of the iliofemoral veins up to the inferior vena cava is possible and the procedure has been described by Ing and associates [170,171]. Immediate and follow-up results look satisfactory [172] as documented in one study; 70 systemic venous stents were placed in 33 patients and a significant increase in vessel diameter was observed.…”
Section: Systemic Veinsmentioning
confidence: 99%
“…Very rarely is this symptomatic, manifesting lower-extremity ectasia or prominent lower abdomen superficial veins. 613 The deep femoral veins remain patent, and venous collaterals will drain blood, bypassing the stenosis, often via the internal iliac vein and paravertebral venous system. Because femoral venous thrombosis is most often clinically silent, the true incidence is unknown.…”
Section: Incidence and Significance Of The Problemmentioning
confidence: 99%
“…Ing et al 613 have reported successful late transcatheter rehabilitation of femoral vein thrombosis identified at a followup cardiac catheterization with implantation of stents in 24 patients. Although guidewires were easily passed across the stenotic vessels, occluded vessels required puncture through the thrombosed sites with a stiff wire or transseptal needle.…”
Section: Post-cardiac Catheterization Venous Thrombosismentioning
confidence: 99%
“…These techniques have been described in patients with congenital heart disease requiring access for catheterization by one of the authors (F.F.I.) 17,18 but not in children with other chronic illnesses. We illustrate with this case that these techniques can preserve life-sustaining access sites in chronically ill and prothrombotic, PN-dependent patients.…”
Section: Figurementioning
confidence: 99%